Outcome of limited‐stage peripheral T‐Cell lymphoma after CHOP(−like) therapy: A population based study of 239 patients from the Nordic lymphoma epidemiology group. Issue 3 (1st January 2023) - Ludvigsen Al‐Mashhadi, Ahmed; Cederleuf, Henrik; Kuhr Jensen, Rasmus; Holm Nielsen, Torsten; Bjerregård Pedersen, Martin; Bech Mortensen, Thomas; Relander, Thomas; Jerkeman, Mats; Ortved Gang, Anne; Kristensen, Anne Louise; Roost Clausen, Michael; de Nully Brown, Peter; et al.
Abstract: Peripheral T‐Cell Lymphomas (PTCLs) are rare, aggressive lymphomas with poor outcomes, but limited‐stage disease is infrequent and not well‐described. This study reports outcomes and prognostic factors in limited‐stage nodal PTCLs in a binational population‐based setting. Patients were identified from the Danish and Swedish lymphoma registries. Adults diagnosed with limited‐stage nodal PTCL (stage I‐II) and treated with CHOP(−like) therapy ±radiotherapy between 2000 and 2014 were included. Medical records were reviewed by local investigators. A total of 239 patients with a median age of 62 years were included; 67% received 6–8 cycles of CHOP(−like) therapy and 22% received 3–4 cycles, of which 59% also received radiotherapy. Autologous stem cell transplant consolidation was administered to 16% of all patients. Median follow‐up was 127 months with 5‐years overall survival (OS) of 58% (95% CI: 53–65) and progression‐free survival (PFS) of 53% (95% CI: 47–59). In multivariable analysis, age ≥ 60 years and B‐symptoms were unfavorable and ALK+ anaplastic large cell T‐Cell lymphoma was favorable for survival outcomes. There was no difference in treatment‐specific outcome (3–4 cycles vs. 6–8 cycles of CHOP(−like) ± radiotherapy). Low‐risk patients (age < 60 without B‐symptoms) had a 5‐year OS of 77% (95% CI 67–89%). In the present study of limited‐stage nodal PTCL, survival after curative intent chemotherapy +/− radiotherapy was inferior to that of limited‐stage diffuse large B‐cell lymphoma, but a subgroup of young patients without B‐symptoms had very good outcomes. Treatment outcomes after 3–4 cycles versus 6–8 cycles of CHOP(−like) therapy were comparable.